The Oslo Health Study: The impact of self-selection in a large, population-based survey - Bjertness Espen; Selmer Randi; Søgaard Anne; Thelle Dag (BMC, 2004)
Abstract Background Research on health equity which mainly utilises population-based surveys, may be hampered by serious selection bias due to a considerable number of invitees declining to participate. Sufficient information from all the non-responders is rarely available to quantify this bias. Predictors of attendance, magnitude and direction of non-response bias in prevalence estimates and association measures, are investigated based on information from all 40 888 invitees to the Oslo Health Study. Methods The analyses were based on linkage between public registers in Statistics Norway and the Oslo Health Study, a population-based survey conducted in 2000/2001 inviting all citizens aged 30, 40, 45, 59-60 and 75-76 years. Attendance was 46%. Weighted analyses, logistic regression and sensitivity analyses are performed to evaluate possible selection bias. Results The response rate was positively associated with age, educational attendance, total income, female gender, married, born in a Western county, living in the outer city residential regions and not receiving disability benefit. However, self-rated health, smoking, BMI and mental health (HCSL) in the attendees differed only slightly from estimated prevalence values in the target population when weighted by the inverse of the probability of attendance. Observed values differed only moderately provided that the non-attending individuals differed from those attending by no more than 50%. Even though persons receiving disability benefit had lower attendance, the associations between disability and education, residential region and marital status were found to be unbiased. The association between country of birth and disability benefit was somewhat more evident among attendees. Conclusions Self-selection according to sociodemographic variables had little impact on prevalence estimates. As indicated by disability benefit, unhealthy persons attended to a lesser degree than healthy individuals, but social inequality in health by different sociodemographic variables seemed unbiased. If anything we would expect an overestimation of the odds ratio of chronic disease among persons born in non-western countries.